Comparative Evaluation of Bromhexine HCl Mucoadhesive Microspheres Prepared by Anionic, Cationic and Nonionic Polymers - Limpa, Sabirah Ishaque; Islam, Zahirul; Reza, Md Selim (Bangladesh Pharmaceutical Journal, 2020)
The purpose of this study was to formulate and assess the mucoadhesive microspheres of bromhexine hydrochloride, a mucolytic agent, using three different types of polymers to achieve gastric retention for improved solubility and bioavailability of the drug. The mucoadhesive formulation was prepared because it dissolved in the pH range of 1 to 4. The characteristics of the prepared microspheres were evaluated by determining the particle size, percent drug loading, surface morphology, swelling behavior, mucoadhesive bond strength and drug entrapment efficiency. The in vitro dissolution was studied using the USP dissolution apparatus I in 0.1N HCl (pH 1.2) media for 8 hours. The release kinetics were analyzed by using zero order, first order, Higuchi, Korsmeyer-Peppas and Hixon-crowell equations to explain the release mechanism from the microspheres. The microspheres exhibited good swelling index and the drug entrapment efficiency was above 79 % for all the formulations. All the formulations showed drug release above 25%, 35%, 50% and 75% after 2 hrs, 4 hrs, 6 hrs and 8 hrs of dissolution respectively. The mucoadhesive bond was observed up to 8 hrs in acidic media. The surface morphology of the prepared microspheres was studied by Scanning Electron Microscope (SEM) and no interaction was found between drug and polymer from the FTIR study. Bangladesh Pharmaceutical Journal 23(2): 117-124, 2020